Literasi Keuangan, Media Sosial dan Perilaku investasi Instrument Keuangan Syariah Generasi Muda dikota Padang - Riski, Tri Rachmat; Sulistianingsih, Henny; Maivalinda, Maivalinda (Universitas Dharma Andalas, 2024)
Investment behavior tends to be influenced by individuals' ability to process information related to the uncertainty of the risks they will face. Individuals' ability to respond to risk uncertainty is greatly influenced by their knowledge of the investment sector they will manage. Knowledge supported by measurable analytical skills is expected to provide considerations in making better investment decisions in the future. This study aims to determine the literacy of Islamic finance and the role of social media in influencing the investment behavior of Islamic financial instruments among the younger generation in the city of Padang. This research is also expected to contribute to developing relevant concepts and approaches to financial studies in improving Islamic financial literacy related to directing investment behavior in Islamic finance. The object of this research is the younger generation represented by students who already have knowledge and information about Islamic finance in the city of Padang. The data analysis technique used in this research is the structural equation model. The results show that financial literacy positively influences Islamic financial investment behavior, and social media significantly influences investment behavior as a mediating variable for Islamic financial instrument investments. Abstrak Perilaku investasi cendrung dipengaruhi oleh kemampuan individiu dalam mengolah informasi terkait ketidakpastian resiko yang akan dihadapi. Kemampuan individu dalam mensikapi ketidakastian resiko sangat dipengarui oleh pengetahuan individu atas sektor investasi yang akan dikelola. Pengetahuan yang didukung dengan kemapuan analisis yang terukur diharapkan mampu memberikan pertimbangan dalam proses pengambilan keputusan investasi yang lebih baik dimasa mendatang. Penelitian ini bertujuan untuk mengetahui literasi keuangan syariah dan peran media sosial dalam mempengaruhi perilaku investasi instrument keuangan syariah pada generasi muda dikota padang. Penelitian ini juga diharapkan mampu memberikan kontribusi dalam mengembangkan konsep serta pendekatan studi keuangan yang relevan dalam meningkatkan literasi keuangan syariah terkait dalam mengarahkan perilaku investasi keuangan syariah. Objek penelitian ini adalah generasi muda yang diwakili oleh mahasiswa yang telah memiliki pengetahuan dan informasi tentang keuangan syariah dikota Padang. Teknik analisis data yang digunakan ada penelitian yaitu model persamaan structural. Hasil penelitian memperlihatkan literasi keuangan secara positif memberikan pengaruh terhadap perilaku investasi keuangan syariah dan media sosial secara signifikan memberikan pengaruh sebagai variabel mediasi perilaku investasi instrumen keuangan syariah.